2019
DOI: 10.3390/polym11060937
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Engineering Thermoplastics: Poly(butylene 2,5-furandicarboxylate) Blends

Abstract: Poly(butylene 2,5-furandicarboxylate) (PBF) constitutes a new engineering polyester produced from renewable resources, as it is synthesized from 2,5-furandicarboxylic acid (2,5-FDCA) and 1,4-butanediol (1,4-BD), both formed from sugars coming from biomass. In this research, initially high-molecular-weight PBF was synthesized by applying the melt polycondensation method and using the dimethylester of FDCA as the monomer. Furthermore, five different series of PBF blends were prepared, namely poly(l-lactic acid)–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…Calling in mind that δ = 22.2 for PBF and 21.6 (MJ/m 3 ) 1/2 for PCHDMF, it is reasonable to suppose that PCHDMF-PBF blends can be miscible or at least partially miscible. We should note, at this point, that in a previous study PET-PBF blends were also found to show single composition dependent glass transition, while δ = 22.2 for PBF and 22 (MJ/m 3 ) 1/2 for PET [62]. PPT-PBF blends, however, (δ = 22.2 for PBF and 21.5 (MJ/m 3 ) 1/2 for PPT) showed dual glass transitions.…”
Section: Ppf and Pbf Blendsmentioning
confidence: 54%
See 2 more Smart Citations
“…Calling in mind that δ = 22.2 for PBF and 21.6 (MJ/m 3 ) 1/2 for PCHDMF, it is reasonable to suppose that PCHDMF-PBF blends can be miscible or at least partially miscible. We should note, at this point, that in a previous study PET-PBF blends were also found to show single composition dependent glass transition, while δ = 22.2 for PBF and 22 (MJ/m 3 ) 1/2 for PET [62]. PPT-PBF blends, however, (δ = 22.2 for PBF and 21.5 (MJ/m 3 ) 1/2 for PPT) showed dual glass transitions.…”
Section: Ppf and Pbf Blendsmentioning
confidence: 54%
“…A very slight shift in the T g values is not enough to indicate significant homogenization ( Figure 3c). Again, from FTIR measurements, the blend retains characteristics of both polyesters, meaning that the C=O stretching at 1742 cm −1 (present in both neat polymers), the angular deformation of aromatic C-H at 830 cm −1 (present in PEF only), terminal hydroxyl groups at 3446 cm −1 (PEF) and the characteristic 2,5-disubstituted furan heterocycles of PEF at 3125 cm −1 (Figure 3d Previous works from our group focused on the study of blends of PEF with PPF or PBF [57][58][59]62]. It was found that the PPF-PEF blends show a single glass transition.…”
Section: Pef Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, copolyesters are developed rapidly due to the synthesis of new bio-based monomers and polymers. 2,5-furandicarboxylic acid is a popular bio-based aromatic diacid monomer consisting of a furan ring to replace the terephthalate acid, achieving an excellent gas barrier property [19][20][21][22][23]. Otherwise, the cross-linking modifiers are frequently undertaken to improve the thermal and mechanical properties of bio-based copolyesters [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Ở đây, có một peak thu nhiệt đáng chú ý tại 159 ºC (peak temp tại 167 ºC), tương ứng với điểm nóng chảy của PBF. Kết quả này tương đương với mẫu PBF được Poulopoulou và đồng nghiệp tổng hợp gần đây với điểm nóng chảy tại khoảng 160 o C [16].…”
Section: Phân Tích Nhiệt Quét VI Sai Dscunclassified